Integration of an Objective Approach Focused on the Consumer to Evaluate the Quality of Processed Brussels Sprouts - Olivera, Daniela Flavia (2011)
Few research works focus on integration of the objective analysis of frozen vegetable quality and the preference of consumers for these products. The aim of the present work was to investigate the consumption patterns of Brussels sprouts, the degree of importance that consumers give to main attributes, and the constructions they make about product quality. For this aim, a series of surveys (snowball sampling method) were performed with consumers from four cities in Argentina. Also, the effect of different industrial operations (two blanching procedures, freezing and cooking) on texture, color, total chlorophyll content and ascorbic acid content of processed sprouts, was determined with respect to the fresh product. A function Z (overall quality) was defined to integrate the information obtained by both approaches. Taking into account the relative importance assigned by surveyed consumers to appearance, texture and nutrient content, the quality of final product obtained from different processing methods was equivalent. Most consumers, 96% of total, preferred the fresh product, which suggests that prejudging by consumers influences attempts at objective estimation of quality.